Benefits and barriers of partnering to quantity surveying firms / Hamimah Adnan ... [et al.] - Adnan, Hamimah; Mohd Taip, Amirul Zaki; Rosman, Muhammad Redza; Bandi, Shamsulhadi (Faculty of Architecture, Planning and Surveying, 2016)
This paper is to identify the implementation of partnering, its effects and possible strategies to be employed from the point of view of quantity surveyors. Both quantitative and qualitative research approaches were adopted to obtain relevant information to meet the objectives of the research. Two hundred and fifty (250) sets of questionnaires were distributed to registered quantity surveyors in the Klang Valley, Malaysia and forty (40) of them were returned and analysed. Subsequently, interviews were carried out with ten (10) experienced quantity surveyors to gather detailed information regarding their experience on partnering work. It was found that most of the quantity surveyors feel that the partnering are suitable to be implemented by quantity surveying firms and partnering should be promoted among the quantity surveyors to ensure the sustainable growth of the profession in the Malaysian construction industry